2016
DOI: 10.1016/j.vaccine.2016.10.060
|View full text |Cite
|
Sign up to set email alerts
|

The TB vaccine H56+IC31 dose-response curve is peaked not saturating: Data generation for new mathematical modelling methods to inform vaccine dose decisions

Abstract: These results suggest that the highest, safe dose may not always optimal in terms of immunogenicity, as the dose-response curve may not saturate. Detailed longitudinal dose range data for TB vaccine H56+IC31 reveals response dynamics in mice that should now be used to identify optimal doses for humans using clinical data, using new data collection and mathematical modelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 22 publications
0
32
0
Order By: Relevance
“…IS/ID modelling was applied to determine the dose-response curve and showed a definitive n-shape for multiple times points after vaccination [11]. This strongly suggests that the predicted best dose is likely to be lower than previously investigated [11]. Preliminary work has also been conducted to simulate further responses (based on these empirical data) to obtain optimal dosing cohorts and narrow the confidence interval around predicted best dose.…”
Section: Current Is/id Modellingmentioning
confidence: 99%
“…IS/ID modelling was applied to determine the dose-response curve and showed a definitive n-shape for multiple times points after vaccination [11]. This strongly suggests that the predicted best dose is likely to be lower than previously investigated [11]. Preliminary work has also been conducted to simulate further responses (based on these empirical data) to obtain optimal dosing cohorts and narrow the confidence interval around predicted best dose.…”
Section: Current Is/id Modellingmentioning
confidence: 99%
“…Recently developed mathematical modelling methods, referred to as immunostimulation/immunodynamic (IS/ID) modelling, attempts to address these issues [7][8][9][10]. IS/ID modelling was developed to address the lack of quantitative methods in vaccine development [11].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of IS/ID is to translate pharmacokinetic/pharmacodynamic (PK/PD) methodology to vaccine development, and preliminary IS/ID modelling has shown promise in accelerating vaccine dosing decisions. Modelling of the dose-response curve and cross-species translation of tuberculosis vaccine dosing data have predicted a lower human dose than previously tested [7,9], and showed that antibody response against human parainfluenza virus may be maximised by an intermediate dose [12]. To inform future IS/ID modelling, dose-response data must be collated.…”
Section: Introductionmentioning
confidence: 99%
“…A peaking relationship implies that there exists some dose for which the response is maximised, and that an increase in dose would lead to a decreased response. Historically, pre-clinical trials typically have made the assumption of a saturating curve shape [6]; however, research has shown that for both tuberculosis and influenza vaccines a peaking shape may better describe the dose-response curve [7,8]. Adenoviral vaccine dose-response curve shape has not yet been established.…”
Section: Introductionmentioning
confidence: 99%